30-Year High Cardiovascular Risk Incidence and its Determinants: CUME Study - Renata Soares Passinho; Josefina Bressan; Helen Hermana Miranda Hermsdorff; Fernando Luiz Pereira de Oliveira; Adriano Marçal Pimenta (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: Estimate the incidence of the 30-year high cardiovascular risk and its determinants among graduates of federal universities in Minas Gerais. Methods: This is a prospective cohort of 2,854 adults aged 20 to 59. The incidence of the outcome was calculated using the Framingham equation and its determinants were determined through multivariate Cox regression. Results: After an average of 2.62 years, the incidence of high cardiovascular risk was 8.09 and 20.1 cases per 1,000 person-years, for females and males respectively. Being male (HR: 2.34; 95% CI: 1.58 - 3.46), employment (HR: 2.13; 95% CI: 1.13 - 3.99), high consumption of processed foods (HR: 2.44; 95% CI: 1.21 - 4.90), and being physically active (HR: 0.63; 95% CI: 0.41 - 0.98) were associated with high cardiovascular risk. Conclusions: Among highly educated adults, being male, employment, and high consumption of processed foods are predictors of high cardiovascular risk, while being physically active acts as a protective factor.